Wireless Patient Monitoring System - Hashim, Nik Mohd Zarifie; Sizali, Muhammad Syahmi (IJSR, 2013)
The development of wireless patient monitoring system has been quite intensive in the past decade. Hence, in the present study, a new approach of wireless patient monitoring system was proposed as a prototype to minimize the power consumption and the costing issue. Visual Basic Net. 2010 as the software and Peripheral Interface Controller (PIC) 16F877 microcontroller as the hardware circuit were used to implement the system. The communication between the hardware and software systems is in the full duplex communication via the XBee modules happened. The results show that XBee module is successfully communicated with the whole system and the monitoring software is in the best condition to be implemented. Since the prototype using variable voltage, good comparison with the experimental and previous